ANALISIS KEBUTUHAN LEMBAGA PENELITIAN DAN PENGEMBANGAN (LITBANG) DI KABUPATEN BANDUNG - Rizki Hegia Sampurna; Irwandi Irwandi (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
Research and development (R &D) plays a pivotal role in the process of national and regional development. National and local  board of research and development are expected to be a think thank in the whole process of policy making, formulation and implementation. It is also the case with Bandung regency wherein local development is running rapidly and,thus, demenading a more research-based policy. This study is set to analyze the needs for initiating an independent local  board of reasearch and development in the Bandung  regency in order to support the implentation of development plan. Trangulation is deployed as a proper method in the investigation to explore the aspiration or opinion of all stakeholders in local  government of Bandung. The study reveals that based on the assessment of legal norms and government vision, mission and strategic plans (RPJMD), Bandung regency needs an independent board of research and development. While the survey conducted to 39 local government departments (SKPD) in Bandung shows that 94,9% of them do not recommend an independent board. The follow-up indepth interview indicates that the gap between two results is due to lack of understanding and commitment among the government employees and stakeholders on the important role of research and develompment in the governmental works.